2009
DOI: 10.1287/mnsc.1080.0899
|View full text |Cite
|
Sign up to set email alerts
|

Top Management Team Diversity and Firm Performance: Moderators of Functional-Background and Locus-of-Control Diversity

Abstract: Past research on the relationship between top management team (TMT) compositional diversity and organizational performance has paid insufficient attention to the nature of TMT team processes in interaction with TMT diversity. We fill this gap by studying how three team mechanisms (collaborative behavior, accurate information exchange, and decision-making decentralization) moderate the impact of TMT diversity on financial performance of 33 information technology firms. We focus on two fundamentally different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
238
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(263 citation statements)
references
References 70 publications
10
238
0
1
Order By: Relevance
“…Different studies have shown that senior management have an essential role in the implementation of strategic changes in organizations, such as the changes required for quality culture implantation (Boone & Hendricks, 2009;Bourgeois & Eisenhardt, 1988;Carmeli & Halevi, 2009). In fact, Salaheldin (2009) found results that prove the importance of top management commitment for the implementation of quality programs.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that senior management have an essential role in the implementation of strategic changes in organizations, such as the changes required for quality culture implantation (Boone & Hendricks, 2009;Bourgeois & Eisenhardt, 1988;Carmeli & Halevi, 2009). In fact, Salaheldin (2009) found results that prove the importance of top management commitment for the implementation of quality programs.…”
Section: Discussionmentioning
confidence: 99%
“…Team members can attain this sort of knowledge by interacting frequently with other team members and exchanging information [4]. Because each TMT has members with diverse backgrounds [59], a variety of social and environmental knowledge and information exists within a TMT [60]. Thus, a behaviorally integrated TMT has a higher capacity to assimilate and incorporate social and environmental information into its decision making.…”
Section: Behavioral Integration and Sustainabilitymentioning
confidence: 99%
“…While it is sometimes noted that TMT heterogeneity can be a 'double edged sword' (Hambrick, Cho, & Chen, 1996), there is now a substantial body of research highlighting the way these cognitive, symbolic and communicative consequences of heterogeneity impact on performance (Boone & Hendriks, 2009;Bunderson, 2003;Carpenter, 2002). For example, using a panel of 1,489 U.S. firms from 1999 to 2011, Harjoto, Laksmana, & Lee (2014) conclude that more heterogeneous boards are positively associated with increasing corporate social responsibility performance.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Although the findings of some studies are mixed (Homberg & Bui, 2013;Carmeli & Sheaffer, 2009), the balance of evidence suggests that demographic characteristics of TMT do have many positive consequences for organisations (Boone & Hendriks, 2009;Harjoto, Laksmana, & Lee, 2014;Naranjo-Gil, Hartmann, & Maas, 2008). These effects, in turn, are frequently explained by the cognitive, symbolic and communicative impact of more heterogeneous management teams, improving both the quality of strategic decisions and the likelihood that they will be translated and implemented (Milliken & Martins, 1996).…”
Section: Introductionmentioning
confidence: 99%